Factors Affecting People’s Participation and Implementation of Institution-Village Linkage Programme in Sunderbans, West Bengal (Indian Journal of Extension Education, 2012)
Institution -Village Linkage Programme (IVLP) was conceived of the philosophy of participatory research in the technology generation process. entral Soil Salinity Research Institute implemented IVLP in two villages of Sunderban . Several factors affect people’s participation in any development programme.Ahigh degree of participation is not usually possible from the outset.Extent of people’s participation in IVLP programme was moderate.The study revealed that motivational factors, social credibility of the programme, family support, need for information, input etc.promote people’s participation in IVLP.